THE USE OF FIGURATIVE LANGUAGE IN CHARACTERIZATION OF WILDE’S THE NIGHTINGLE AND THE RED ROSE - Fitria Lonada; Laily Martin (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2015)
The study suggests how figurative language is related to the description of characterization in children litera-ture. To ensure that the indirectness of the figurative language actually helps describing characterizations further, the study focuses on the description of the simile, metaphor, personification, hyperbole, and irony (Rozakis, 1999) of the main characters of Wilde’s The Nightingale and the Rose. The analysis on the figura-tive language uses is used as the base for interpreting the story’s characterization. It reveals that figurative language describes characterization relating to the information on the characters’ mental and physical attrib-utes. Each of the figurative language categories describes the characterization in certain way in order to make the particular abstract concepts for characterization detailed and concrete. In that case, with the help of figu-rative language, the story may be comprehended better by young readers. Keywords: figurative language, characterization, simile, metaphor, personification, hyperbole, irony